Bifunctionally engineered polyethylenimines as efficient DNA carriers and antibacterials against resistant pathogens. (September 2018) - Ahmadi, Z; Jha, D; Kumar, B; Gautam, HK; Kumar, Pradeep
In this study, we have designed and developed two series of bifunctional conjugates by tethering polyethylenimine with streptomycin. By varying the amount of streptomycin, conjugates, polyethylenimine-streptomycin, have been synthesized and characterized spectroscopically. Gel electrophoresis assay revealed a slight decrease in the cationic charge density on the conjugates as these retarded the mobility of pDNA at higher w/w ratios. Further, transfection studies showed that both the series of conjugates transfected the mammalian cells efficiently with low-molecular weight polyethylenimine-streptomycin conjugates were more competent (∼9-fold enhancement with respect to native bPEI) exhibiting high cell viability too. Besides, both the series of conjugates displayed excellent antibacterial activity on pathogenic bacteria, even better than native streptomycin on resistant strains. Altogether, these results ensure the promising potential of the projected bifunctional conjugates as safe and efficient gene delivery vectors as well as antibacterials for future biomedical applications.